Automation and manufacturing for the built environment - Thompson, Steve (Emerald Publishing Limited, 2025)
Automation and Manufacturing for the Built Environment is a plain-language guide to the application of automation and manufacturing technologies and processes to the delivery and operation of the built environment. Covering the full asset lifecycle, the book provides a straightforward guide to a wide range of technologies, showing where they fit and the benefits that they have, with real-world examples of their applications. Coverage in the book includes new models to assess the potential benefits and impacts of new technologies, and to consider their implications how automation and manufacturing-led approaches can complement each other to address longstanding construction industry challenges overview of automation and manufacturing technologies likely to offer greatest value in the short, medium and long-term "no-regret" decisions that can be made today that will be of value in the future, including development of structured product data, logical data models and use of generative design tools the crucial roles of planning and connectivity between technologies 2035 scenarios based on adoption of different automation and manufacturing-led models. The book also presents assessments on the potential levels of automation that different technologies are likely to deliver up to 2035, the wider benefits they can deliver and impacts on the future of work. Automation and Manufacturing for the Built Environment will be of interest to a wide range of construction professionals seeking information in the very latest developments in the industry, including clients; senior managers; digital leads, information and BIM managers; engineers; architects; and planners. It is equally applicable to small and large enterprises.
Includes index.
Keywords: Built environment.; Automation.; Production management.; Technology & Engineering -- Automation.; Manufacturing industries.; Automatic control engineering.; elektronické knihy; electronic books